REDESIGN OF A KAMPUNG HOUSE IN SIRNAGALIH VILLAGE, TAMANSARI DISTRICT, BOGOR REGENCY WITH A HEALTHY HOUSE APPROACH - Rita Laksmitasari Rahayu (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2021)
The location of Community Service at the foot of Mount Salak is precisely in Sirnagalih Village, RT.1/11, Tamansari District, Bogor Regency. The houses of Sirnagalih Village residents must be able to protect their residents from cold and humid air. Residents of the location as partners provide information about their residents who need to improve the quality of their housing in order to live a healthier life. The criteria for recipients of assistance are elderly residents with housing conditions that can have an unfavorable impact on residents. The result of the redesign is one of the residents' houses as an example for other residents who have similar houses. The Community Service Team offered a solution by redesigning the less suitable residential building into a healthy and simple house using building materials provided by residents independently. The redesign uses a building reliability approach that consists of aspects of safety, health, comfort, and ease of movement. This activity uses several methods according to the activity stage, such as observation, physical measurements of buildings, interviews with partners, architectural design, presentation, and design implementation. The conclusion of the activity is that the result of the redesign has a good impact on partners, the benefits of the principle of mutual cooperation, making healthy homes need not be expensive. Suggestions for this activity are residents who build houses must always use a healthy home approach and always care about the health of their environment.Keywords: healthy house, redesign, elderly, building reliability